2017
DOI: 10.1007/s00221-017-5158-2
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of lateral peripersonal space is linked to handedness

Abstract: The space immediately surrounding our bodies, i.e., peripersonal space (PPS), is a critical area for the interaction with the external world, be it to deal with imminent threat or to attain objects of interest. In the brain, a dedicated system codes PPS in motor terms for the purpose of action. Yet, humans have asymmetric motor abilities: the dominant hand has an advantage in term of movements' precision and reaction time. Furthermore, spatial attention is asymmetric and seems to be linked to a right hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
3
19
0
Order By: Relevance
“…Thus, PPS might not be an inor-out zone. In line with this result, previous studies suggested that, within PPS, the distance between an auditory or visual stimuli continues to influence tactile detection (de Haan et al, 2016;Hobeika et al, 2018) and action preparation (Camponogara et al, 2015) This logarithmic function is also coherent with the theoretical framework proposed by Bufacchi and Iannetti, who described PPS as an action field, in which responses are graded with proximity (Bufacchi and Iannetti, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, PPS might not be an inor-out zone. In line with this result, previous studies suggested that, within PPS, the distance between an auditory or visual stimuli continues to influence tactile detection (de Haan et al, 2016;Hobeika et al, 2018) and action preparation (Camponogara et al, 2015) This logarithmic function is also coherent with the theoretical framework proposed by Bufacchi and Iannetti, who described PPS as an action field, in which responses are graded with proximity (Bufacchi and Iannetti, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…All of them were right-handed. As PPS is linked to handedness (Hobeika et al, 2018), participants' handedness was verified with a questionnaire measuring skilled hand preference. The scores on this questionnaire, called the Flinders Handedness survey (FLANDERS) (Nicholls et al, 2013), range from -10 for strong left-handed individuals to +10 for strong right-handed individuals.…”
Section: Materials and Methods 21 Participantsmentioning
confidence: 99%
“…Thus, PPS might not be an in-or-out zone. In line with this result, previous studies suggested that, within PPS, the distance between an auditory or visual stimuli continues to influence tactile detection (de Haan et al, 2016;Hobeika et al, 2018) and action preparation (Camponogara et al, 2015) This logarithmic function is also coherent with the theoretical framework proposed by Bufacchi and Iannetti, who described PPS as an action field, in which responses are graded with proximity (Bufacchi and Iannetti, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Although, asymmetries in left and right PPS have been revealed before. One study showed that right-handed people have a larger PPS on their left side, whereas left-handed people have a similar PPS for both sides of the body (Hobeika, Viaud-Delmon, & Taffou, 2018). Moreover, people who have had an upper limb amputation have a smaller PPS around the stump than for the intact limb (Canzoneri et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%